THE DEVELOPMENT OF SUPER CHEM GAME ORIENTED ANDROID AS INSTRUCTIONAL MEDIA ELECTROLYTE AND NON ELECTROLYTE - Rahmawati, Annisa; Lutfi, Achmad (JCER (Journal of Chemistry Education Research), 2018)
This study aim to discover the advisability of Super Chem (Super Chemistry) Game as instructional media on Electrolyte and Non ElectrolyteSolution Matter. The game was feasible if fullfill 3 criteria that is validity, practicality, and effectiveness.? Validity determined from the validation results of the game, the practicality determined from the result of percentage of student's response questionnaire, and effectiveness determined from student's learning outcomes and student?s activity. This research using Research and Development (R&D) research method. This game is tested to 15 students from class X at SMAN 1 Kamal Bangkalan. The validity from result the validation is 91.11%. Practicality from result of student's response is 94.11%, and effectiveness from result of observation activity of students as many as 13 students successfully complete level 1-4 well and increase learning outcomes that is 100%.